2018
DOI: 10.1080/15548627.2018.1458174
|View full text |Cite
|
Sign up to set email alerts
|

Silica nanoparticles induce autophagosome accumulation via activation of the EIF2AK3 and ATF6 UPR pathways in hepatocytes

Abstract: Autophagy dysfunction is a potential toxic effect of nanoparticles. Previous studies have indicated that silica nanoparticles (SiNPs) induce macroautophagy/autophagy dysfunction, while the precise mechanisms remain uncertain. Hence, the present study investigated the molecular mechanisms by which SiNPs enhanced autophagosome synthesis, which then contributed to autophagy dysfunction. First, the effects of SiNPs on autophagy and autophagic flux were verified using transmission electron microscopy, laser scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 56 publications
7
42
0
Order By: Relevance
“…The latter study was also the first to show that silica nanoparticles accumulate within the smooth endoplasmic reticulum (ER) and, by this, seem to induce ER-autophagy. This finding was recently confirmed by electron microscopy for hepatocytes [71], in which autophagosome accumulation involved the activation of the EIF2AK3 and ATF6 UPR pathways. Together these studies suggest that SAS nanomaterials have a similar mode of action on different cell types via the lysosomal pathway.…”
Section: Resultssupporting
confidence: 55%
“…The latter study was also the first to show that silica nanoparticles accumulate within the smooth endoplasmic reticulum (ER) and, by this, seem to induce ER-autophagy. This finding was recently confirmed by electron microscopy for hepatocytes [71], in which autophagosome accumulation involved the activation of the EIF2AK3 and ATF6 UPR pathways. Together these studies suggest that SAS nanomaterials have a similar mode of action on different cell types via the lysosomal pathway.…”
Section: Resultssupporting
confidence: 55%
“…The increased expression of enzymes with antioxidant potential, also provide evidence for the activation of protective mechanisms induced by an abnormal amount of ROS generated within the cells. Activation of gene expression associated with the formation of autophagosomes (LAMP1, RAB24, GUSB) is also consistent with this phenomenon 24 . It should be noted however, that patients despite the increased formation of autophagosomes in T1D, the process of removing damaged proteins through autophagy is inefficient due to the inhibition of lysosomal hydrolysis 25 .…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, SFN-Cys did not aggravate the upregulation of LC3II/LC3I in the present of chloroquine, suggesting SFN-Cys might inhibit either the fusion of autophagosomes to lysosomes or lysosomal degradation capacity. Whereas both immunofluorescence staining and co-immunoprecipitation results supported that SFN-Cys enhanced the fusion of autophagosome to lysosome in GBM 38 . Luckily, we identified that SFN-Cys downregulated both the lysosomal cysteine proteases Cathepsin D and TPP1 in the whole cell and Cathepsin 1 L in mitochondria by HPLC–MS/MS analysis.…”
Section: Discussionmentioning
confidence: 69%